Commodity analysis of compression products for varicose veins - Tetiana Diadiun; Inna Baranova; Svitlana Kovalenko; Rymma Yeromenko; Mykola Rybalkin (Pensoft Publishers, 2021)
Compression therapy occupies a key place in the complex treatment and prevention of chronic venous insufficiency of the lower extremities. Today the pharmaceutical market of Ukraine is represented by a wide range of compression products. Popular in Ukraine are manufacturers of compression products from the Baltic region, Ukraine, there are also Russian, but leading in quality are Germany, USA, and Italy. A survey of consumers and pharmacy practitioners has been performed. The results obtained indicate that compression products for varicose veins treatment are inferior to medicinal products in sales. The main motive for buying a compression product is a doctor's prescription. The most popular compression garments are stockings.